The Importance of Management Family-Centered Care Model in Stroke Recovery : A Comprehensive Examination - Ayu, Windri Dewi; Halimatusyadiah, Halimatusyadiah; Jaelani, Ahmad (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2025)
Stroke is a substantial health issue that affects numerous individuals and their families. Stroke survivors and their carers sometimes face difficulties when transitioning from the hospital to their home. Implementing a family-centered care approach throughout rehabilitation is crucial for properly addressing the needs of both parties. Although advantageous, this strategy may give more importance to the worries of family members rather than those of the stroke survivors themselves. The objective of this study was to assess the efficacy of a family-centered care approach in stroke rehabilitation by an analysis of existing research literature and the examination of outcomes. This integrated literature study employs a methodology that investigates databases like Scopus, PubMed, Researchgate, and Google Scholar across several nations such as the United States, Canada, Australia, England, South Korea, the Netherlands, Japan, and others. The results indicated that implementing a family-centered care approach in stroke therapy yielded significant enhancements in the Both groups' physical and mental well-being. The existing body of research suggests that the involvement of family members in the provision of care and support for individuals who have experienced a stroke leads to enhanced outcomes in relation to physical functioning, psychological well-being, and overall quality of life. In stroke rehabilitation, the implementation of a family-centered care approach ultimately leads to favorable outcomes for both stroke patients and their caregivers. Future research should place emphasis on the discovery of specific strategies for effective implementation and the evaluation of the long-term effects of these approaches on persons who have suffered a stroke and their family members.